Ergoespirometria em atletas paraolímpicos brasileiros - Silva, Antonio Carlos da [UNIFESP] (2002)
The purpose of the present article is to discuss the use of incremental exercise test as an important method of functional evaluation of disabled individuals, based on the presentation of the results of the Brazilian athletes that participated in the Sydney Paralympic Games. In addition to the presentation of the analyzed parameters (maximal oxygen uptake - VO2max - and ventilatory anaerobic threshold) for athletes from various sports and types of disability, the physiological basis and methodology used are described. Certain characteristics pertaining to disabled athletes, such as specificity, safeguards, understanding and motivation are explained in the text. Finally, the publication of data regarding this specific group will help the implementation of more effective actions, not only in competitive sports, but also for the rehabilitation of the great contingent of persons with physical and/or mental disabilities in Brazil.